Analysis of the implementation of the healthy Indonesia program policy with a family approach - Abdul Haris; M. Rizki Aditya (Intelektual Pustaka Media Utama, 2026)
This study evaluates the implementation of the Healthy Indonesia Program Family Approach to improve public health and identify inhibiting and supporting factors. This qualitative research employs a case study approach to investigate healthcare dynamics at the Tambora Community Health Center in Bima City, Indonesia. Twelve informants were purposively selected. Data collection involved in-depth interviews, direct observation, and document review, allowing for a multifaceted perspective. An interactive analysis model by Miles and Huberman was used for data analysis, incorporating data collection, reduction, and presentation iteratively. Results showed that 85% of implementing staff had been trained, but there was a shortage of field surveyors, and family visit coverage only reached 72%, below the national target of 80%. Although the average healthy family index of 0.65 indicates adequate results, the main challenges lie in clean living behavior and nutritious diets. The program for mothers giving birth in health facilities reached 95%, but awareness of improving the management of chronic diseases, such as hypertension and tuberculosis, remained low, with treatment fulfillment at 65% and 70%, respectively. The conclusions highlight the need for adaptation strategies and continuous evaluation for the Healthy Indonesia Program to be successful across communities.